Clinical-Anamnestic Features and Evaluation of Control for Exercise-Induced Bronchial Asthma in Schoolchildren with Xenobiotics Biotransformation Genes Polymorphism - O.G. Grygola; O.K. Koloskova (Zaslavsky O.Yu., 2014)
Complex clinical and spirographic investigation of schoolchildren suffering from exercise-induced bronchial asthma was carried out depending on the presence or the absence of genes polymorphism of the enzymes of glutation-S-transferase - GSTT1M1. The study showed that the course of the disease was more severe in the patients with the deletions of the named genes, the reactions of hypersensitivity were more often, but the desobstructive effect during the attack was reached quicker. The self-assessment of the control of the disease by different scales showed the controversial results, but the objectification by the spirographic investigation allowed to define the risk of achieving the controlled course of the disease in children with genotype GSTT1+M1+ (odds ratio - 3.33, relative risk - 1.8, absolute risk - 29 %).